Species profiles life histories and environmental requirements of coastal fishes and invertebrates (Pacific Southwest)--Pacific herring - Barnhart, Roger A. (U.S. Department of the Interior, 1987)
U. S. Fish and Wildlife Service. Biological report ; 82(11.79)